Desarrollo de un prototipo electrónico para el monitoreo de niños dentro de un área establecida en espacios públicos - Flor Bonifaz, Paola Elizabeth (2017)
The monitoring of objects through different electronic systems is widely used, there are currently companies offering small chips or devices tracking and tracing objects based on satellite GPS location technology, but the position error is approximately 10 to 20 Meters with respect to the actual coordinates of the device. Thus the project is based on the implementation of a device that allows children in open places in order to prevent misplacement by the neglect of the substitutes. By conducting initial surveys to define the characteristics of the prototype, it sought a device and technology that adapts to the needs of users, finding as a solution the technology WI-FI (Wireless Fidelity), which allowed the establishment of wireless communication With the monitoring device; Using the parameter RSSI energy indicator that was obtained from the wireless communication, the distance between the electronic monitoring device (DEM) and a smartphone that can perform the administration of the information that the user receives with a graphical system interface Operational Android. An important feature of using WI-FI was that it exhibits stability in the RSSI signal trend and is compatible with most Smart Devices. With the final product, the field tests were performed with the DEM and the application created, obtaining an acceptance of 73% of a population sample of 100 individuals.